2013
DOI: 10.5740/jaoacint.13-227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3M™ Molecular Detection Assay (MDA) Salmonella for the Detection of Salmonella in Selected Foods: Collaborative Study

Abstract: The 3M Molecular Detection Assay (MDA) Salmonella is used with the 3M Molecular Detection System for the detection of Salmonella spp. in food, food-related, and environmental samples after enrichment. The assay utilizes loop-mediated isothermal amplification to rapidly amplify Salmonella target DNA with high specificity and sensitivity, combined with bioluminescence to detect the amplification. The 3M MDA Salmonella method was compared using an unpaired study design in a multilaboratory collaborative study to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…False positive (F pos ) results were obtained in this study, and have also been reported previously for LAMP-based technique (Bird et al, 2013;Vongkamjan et al, 2015). Usually, in order to amplify six to eight target DNA regions, the LAMP employs from four to six primers with much higher concentration than that used in traditional PCR-based methods, which may lead to an increased probability of non-specific amplification induced by formed primer dimers, giving the false positive results (Wang, Brewster, Paul, & Tomasula, 2015).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…False positive (F pos ) results were obtained in this study, and have also been reported previously for LAMP-based technique (Bird et al, 2013;Vongkamjan et al, 2015). Usually, in order to amplify six to eight target DNA regions, the LAMP employs from four to six primers with much higher concentration than that used in traditional PCR-based methods, which may lead to an increased probability of non-specific amplification induced by formed primer dimers, giving the false positive results (Wang, Brewster, Paul, & Tomasula, 2015).…”
Section: Resultssupporting
confidence: 54%
“…Similarly, Martinon et al (2012) reported that the real-time molecular methods (PCR, PMA-PCR) overestimated L. monocytogenes counts on environmental surfaces compared to the culture technique. However, the occurrence of false-positive results may be significantly reduced by avoiding cross-contamination, high humidity and temperatures, when handling reaction tubes and inadequate reaction volumes (Bird et al, 2013;Wang et al, 2015). Nevertheless, apart from a few disadvantages of LAMP technique, it was equally effective as reference ISO method for L. monocytogenes detection, but it reduced significantly the total time of analysis (from minimum 5 days for ISO to less than 2 days including the enrichment time).…”
Section: Resultsmentioning
confidence: 98%
“…The alternative method used 3M Molecular Detection Assay for salmonella tests, which are used with the Molecular Detection System (MDS) for the quick detection of these bacteria in food samples [23]. Premultiplication was carried out in standard peptone buffered water at 37°C within 18-24 h. The procedure related to the use of 3M MDS tests involved the transfer of the multiplied culture to tubes with a lysing solution and lysis for 15 min at 100°C in the first stage, and then a quick cooling within 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The detection of Salmonella cells by the commercial LAMP-based kit (3M Molecular Detection Assay Salmonella; 3M) was performed according to the manufac turer's manual (2). Briefly, 20 pi of BPW enrichment was added to a tube with lysis solution.…”
Section: Inoculation Of Salmonella Cells On Food Samplesmentioning
confidence: 99%
“…Similar to most nucleic acid-based sequence amplification detection methods, this commercial LAMPbased kit does not require costly instrumentation, such as thermal cyclers. LAMP is also characterized by higher specificity and sensitivity, and it significantly shortens the time of DNA amplification due to isothermal reaction conditions (2,5,9).…”
mentioning
confidence: 99%